EARLY MARRIAGE AMONG ROMANI FAMILIES IN SAKARYA - Hasan Hüseyin TAYLAN (Fırat University, 2019)
In this presentation, we propose to unearth and understand the problem of early marriages among Romani children, who get marry in early age that does not fit for their psychological and social situation. In relation to this, in the research, the dimensions of early marriages, their change in terms of time and gender will be outlined and the values among Romanies in terms of marriage and family will be presented. In the light of the aim of this research, the data was obtained by selected Romani families through surveys. 200 Romani families that would present the Sakarya sample were applied a survey via one-by-one talks and these findings were reached to: The age of early marriage among Romanies is 12. Almost half of the marriages are beyond the age of 18. In comparison to boys, girls get marry earlier. They indicate that they get a compassionate marriage and by loving their partners. It was also detected that those who get early marriage cannot continue to their education because of the responsibilities of marriage such as burdening the livelihood. “Kid Bride” is an important problem among Romanies. Similarly, those who continue to their education after marriage are unsuccessful in their school life.